2021
DOI: 10.1186/s12913-021-07347-7
|View full text |Cite
|
Sign up to set email alerts
|

Transition of care in stroke patients discharged home: a single-center prospective cohort study

Abstract: Introduction Approximately two-thirds of the patients admitted to the hospital with an ischemic stroke are discharged directly home. Discontinuity of care may result in avoidable patient harm, re-admissions and even death. We hypothesized that the transfer of information is most essential in this patient group since any future care for these patients relies solely on the information that is available to the care provider responsible at that time. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Second, other risk factors of cerebral infarction, such as blood pressure level, medical history, social economic status, and hospital function were not considered in this study [ 36 , 37 ]. Third, we could not examine patients whose condition worsened after discharge in this study, but previous studies indicated that care after discharge is important [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, other risk factors of cerebral infarction, such as blood pressure level, medical history, social economic status, and hospital function were not considered in this study [ 36 , 37 ]. Third, we could not examine patients whose condition worsened after discharge in this study, but previous studies indicated that care after discharge is important [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to optimize the standard discharge plans that have been commonly used in recent times. This is because, according to a study, there is a significant prevalence of care discontinuity following the discharge of patients who have experienced a first-ever stroke (de Mooij et al 2021). Studies have found that the implementation of discharge planning is frequently limited to the moment when patients leave the healthcare facility.…”
Section: Introductionmentioning
confidence: 99%